2019
DOI: 10.1155/2019/4360525
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Staphylococcus Species Colonization in Healthy and Sick Cats

Abstract: Staphylococcus is one of the most frequently isolated genera of opportunistic bacteria in animals and human beings. Staphylococci in mammals mostly inhabit the skin and mucous membranes. The objectives of the study were to investigate the distribution of staphylococcal species in healthy and sick cats in order to find diagnostic markers. The risk factors associated with colonization were also explored. Isolates from healthy (n=520) and sick cats (n=67) were identified at the species level using matrix-assisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 30 publications
5
59
2
2
Order By: Relevance
“…Researchers point to the fact that conditionally pathogenic microflora can cause a wide range of complications and report that the morbidity, antibiotic resistance of different types of staphylococci in cats depends on the state of the body's defenses. A statistically significant correlation was observed between cat health and staph infection (Bierowiec et al, 2019). The high frequency of colonization of cats by staphylococci is confirmed by Ma et al (2019), who isolated them in 73.8% of animals, which is consistent with the results of our studies.…”
Section: Discussionsupporting
confidence: 91%
“…Researchers point to the fact that conditionally pathogenic microflora can cause a wide range of complications and report that the morbidity, antibiotic resistance of different types of staphylococci in cats depends on the state of the body's defenses. A statistically significant correlation was observed between cat health and staph infection (Bierowiec et al, 2019). The high frequency of colonization of cats by staphylococci is confirmed by Ma et al (2019), who isolated them in 73.8% of animals, which is consistent with the results of our studies.…”
Section: Discussionsupporting
confidence: 91%
“…In this work, SP and SA were detected causing infection in three and two cats, respectively. These species have been formerly recovered from diseased cats [ 1 , 17 ], however, a recent study has reported predominance of other staphylococcal species, such as S. felis and S. haemolyticus , among feline infections [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus pseudintermedius (SP) and Staphylococcus aureus (SA) are harmless colonizers of the skin and mucosa of humans and animals [ 1 ], but they are also frequently implicated in opportunistic infections. In pets, especially in dogs, SP is most frequently detected than SA, both as colonizer and as causative agent of infection.…”
Section: Introductionmentioning
confidence: 99%
“…In Greece, S. lugdunensis was isolated from various infection sites in hospitalized patients (Giormezis et al, 2015 ). Bierowiec et al reported that while most tested S. lugdunensis isolates were susceptible to nine antibiotics (penicillin G, gentamicin, rifampicin, cefoxitin, fusidic acid, trimethoprim/sulfamethoxazole, norfloxacin, clindamycin, and erythromycin), some showed resistance to erythromycin and/or tetracycline via strain-specific carriage of ermC and/or tetK (Bierowiec et al, 2019 ). In addition, a very small number of S. lugdunensis isolates carried SSC mec type IVa.…”
Section: Classification Habitat and Virulence Of Cnsmentioning
confidence: 99%